2000
DOI: 10.1021/jp0005322
|View full text |Cite
|
Sign up to set email alerts
|

FTIR Spectroscopic Investigation of the Mechanism and Kinetics of the Heterogeneous Reactions of NO2 and HNO3 with Soot

Abstract: Soot samples from a spark generator, a flame, and a diesel passenger car were either collected on a Teflon filter and transferred to an IR-transparent window or deposited directly from a flame onto the window and investigated by Fourier transform infrared (FTIR) spectroscopy. The soot-covered windows were mounted in a 10 cm vacuum cell connected to a standard flow system with He as carrier gas. Reactive gases, such as NO2 and HNO3, were added to the carrier gas flow at a concentration of (0.016 to 2.5) × 1014 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
168
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(184 citation statements)
references
References 31 publications
(90 reference statements)
11
168
4
Order By: Relevance
“…As discussed by Jeguirim et al [39] it is attributed to the indicated potential formation of nitric and nitrous acids in presence of water and O 2 . This was also pointed out by Kirchner et al [40], who observed an increase in C-ONO2 and C-ONO groups in the reaction of soot when nitric acid is present in the exhaust flow. In the same way, Uchisawa et al [41] found the cause of the soot oxidation improvement due to water presence in the strong acidity produced by hydrolysis and decarboxylation, as also indicated by Ciambelli et al [42].…”
Section: Dpf Regeneration Behavioursupporting
confidence: 72%
“…As discussed by Jeguirim et al [39] it is attributed to the indicated potential formation of nitric and nitrous acids in presence of water and O 2 . This was also pointed out by Kirchner et al [40], who observed an increase in C-ONO2 and C-ONO groups in the reaction of soot when nitric acid is present in the exhaust flow. In the same way, Uchisawa et al [41] found the cause of the soot oxidation improvement due to water presence in the strong acidity produced by hydrolysis and decarboxylation, as also indicated by Ciambelli et al [42].…”
Section: Dpf Regeneration Behavioursupporting
confidence: 72%
“…13 carbonyl group, assigned to ketone species (1710 cm −1 ), was observed for decane soot. 13,20,21,40,41 As seen in Figure 7, compared to the functional groups on the rich toluene flame soot, no significant changes were observed on the lean toluene flame soot. For n-hexane and decane soot, the lean flame soot exhibited lower intensities in the peaks of alkynesC−H, aromatic C−H, unsaturated CH 2 , and highly substituted aromatic compounds, while the carbonyl (CO) group bound to an aromatic ring showed a larger intensity than that of the rich flame soot.…”
Section: Resultsmentioning
confidence: 91%
“…18 Functional groups, including aliphatic or aromatic C−H, carbonyl CO, and ethers C−O, have been confirmed through infrared spectroscopy. 13,20,21 Microstructures including graphitic carbon, disordered carbon, and amorphous carbon have also been detected using Raman spectroscopy. [15][16][17]19,22,23 Recent studies have shown that residence time in the flame and flame temperature can induce modifications in the microstructures and functional groups of soot.…”
Section: Introductionmentioning
confidence: 99%
“…Those species are present in excess in the mixture (about 100 to 1 NO molecule). But a significant part of NO "disappears", being trapped by C 3 H 6 and its fragments giving R-NO x [18] , adsorbed on the outlet pipes or reduced to N 2 +O 2 . R-NO x formation will be presented in the following section.…”
Section: Characterization Of the Depollution Treatment: Analysis Of Tmentioning
confidence: 99%
“…After it, we will determine the reactional pathways by substituting introduced O 2 by its 18 O 2 isotope. The mass spectrum of the different species created by oxidation from O 2 will indeed be modified.…”
Section: Introductionmentioning
confidence: 99%